Facemask usage and disposal practices from safety and waste perspective / Abirami V. Veeramani - Abirami , V. Veeramani (2021)
COVID-19 has sparked a worldwide emergency and prompted concerns about waste management due to the excessive face mask waste generated globally. Malaysia records over 10 million face masks binned daily and in average a person spends RM180/year on face masks since the pandemic outbreak. Therefore, this study aims to explore the current issues arising from face mask waste from safety and waste dimension in Malaysia. The main objectives of this study are to identify the face mask usage among Malaysian and provide the best safety and waste practices of face mask. Questionnaire and case study analysis have been conducted to collect the data in this study. The questionnaires were distributed to a random population to understand their current practices in wearing face masks, selection preferences and face mask waste management and knowledge level. The data was analyzed using SPSS analytical tool. The result shows that majority (73.3 %) of the respondent agreed choosing face mask that is comfort and fit to their face. Besides, 77.2% of responded agreed that the level of bacterial filtration efficiency (BFE) is important in mask selection. And, around 90 respondents agreed wearing double mask in public spaces. According to 52.8% respondents, N95 masks are most effective in providing protection against COVID-19. 65% respondents are not satisfied with available information of disposal of face masks. Finally, based on the results obtained through the analysis, a guidance was developed to assist users on end-to-end process to improve their management of face mask. Since many nations considering COVID-19 as an endemic phase and thus existence of face mask may prolong longer in usage, this research will assist in developing enhanced public knowledge on safe use and effective face mask waste management for all level of stakeholders.